Parents' intentions toward preschool children's myopia preventive behaviors: Combining the health belief model and the theory of planned behavior - Nan Jiang; Jiayue Chen; He Cao; Yongyi Liu; Yuxin Zhang; Quqin Wang; Ting Wang; Huilan Zhao; Hui Lu; Lei Yang; Jiwei Wang (Frontiers Media S.A., 2022)
ObjectiveThis study aimed to develop an integrated model based on the health belief model (HBM) and the theory of planned behavior (TPB) to explore the influencing factors of parents' intentions toward preschool children's myopia preventive behaviors.MethodsThis cross-sectional study was conducted in Minhang District, Shanghai, China in January 2022. One thousand six hundred and twenty-eight parents of preschool children from seven preschools were recruited in the study. A four-part questionnaire was used to collect data on socio-demographic characteristics, HBM variables, TPB variables and parental intentions. This study used exploratory factor analysis to analyze HBM and TPB items. Hierarchical multiple regression analysis was performed to explore the relationship between independent variables and parents' intentions toward preschool children's myopia preventive behaviors.ResultsThe final integrative model showed that perceived severity, perceived barriers, attitudes, subjective norms, and perceived behavioral control were associated with parents' intentions toward preschool children's myopia preventive behaviors. In model 1, Child's age was entered as a control variable and explained 0.6% of the variance (F = 7.241, p = 0.007). When the HBM variables were entered in model 2, the proportion of variance increased to 25.4% (F = 73.290, P < 0.001). In model 3, TPB variables were entered and explained 63.2% of the variance (F = 246.076, p < 0.001).ConclusionThe integrated model of HBM and TPB constructed in this study significantly improved the degree of explanation of parents' intentions toward preschool children's myopia preventive behaviors. Parents' perceived severity, perceived barriers, attitudes, subjective norms, and perceived behavioral control can be prioritized intervention targets for myopia preventive practices in preschool children.